Selected Works of Willem van Zwet - van de Geer, Sara. (Selected works in probability and statistics, 2012)
With this collections volume, some of the important works of Willem van Zwet are moved to the front layers of modern statistics. The selection was based on discussions with Willem, and aims at a representative sample. The result is a collection of papers that the new generations of statisticians should not be denied. They are here to stay, to enjoy and to form the basis for further research. The papers are grouped into six themes: fundamental statistics, asymptotic theory, second-order approximations, resampling, applications, and probability. This volume serves as basic reference for fundamental statistical theory, and at the same time reveals some of its history. Three Fundamental Statistics Papers -- Asymptotic Statistics -- Second Order Asymptotics -- Resampling -- Applications -- Probabililty.